Graphene Oxide/Polyaniline/Polypyrrole Composite as a Copper Anticorrosive in the Presence of 3.5% NaCl Solution Using RSM - Arguelles Ojeda, J.L; Ovando Medina, V. M. (RIIIT Revista Internacional de Investigación e Innovación Tecnológica, 2026)
Graphene, an atomically thin material discovered only twenty years ago, has become the focus of numerous investigations. Studies show that it has electrical, mechanical, thermal, and optical properties that exceed those of any other known material. In this work, a graphene oxide/polyaniline/polypyrrole (GO/PANI/PPy) composite was synthesized for use in copper coatings to improve their corrosion resistance in the presence of 3.5% NaCl seawater. The optimal proportions of GO to PANI and PPy in the composite to increase the copper corrosion resistance were determined through the Response Surface Methodology (RSM). The composite was characterized by FTIR spectroscopy, thermogravimetric analysis (TGA), and electrical conductivity (CE). FTIR analysis demonstrated that GO, PANI, and PPy are incorporated into the composite, while TGA analysis indicated that the degradation temperature was between 200 and 400 °C, increasing thermal stability with increasing GO content. According to RSM, the samples that exhibited the highest corrosion resistance contained a small amount of GO and a 70/30 weight ratio of PPy/PANI, with a corrosion rate as low as 0.0138 mm/year and an anticorrosion efficiency of 98.66%.
Keywords: Corrosion, Graphene oxide, Polypyrrole, Polyaniline, RSM.